Walka krajów naftowych ze światowym kartelem naftowym - Jankowiak, Ludwik; Makieła, Marek (Wydział Prawa i Administracji UAM, 1969)
The underdeveloped countries which are rich in oil resources are putting up a fight against the exploitation policy of the world oil cartel. The body which is representing their interests is the OPEC organisation (Organisation of Petroleum Exporting Countries). The setting up of this organisation was in fact a response of the oil producing countries to the successive reduction of the information price. OPEC is thus meant to constitute a kind of counterbalance to the world cartel, which is getting most of its crude oil on the territories of the OPEC countries. OPEC represents all Arab countries of the Near East, Venezuela, Indonesia, Libya. In the negotiations with the world cartel the OPEC brings forward numerous postulates. Some of them constitute subjects of this summary. One of the most important and complicated item are the information prices which serve as a basis for computing the royalties due to the governments of the oil producing countries. The next problem evolves around the regulation of the size of crude oil production. There are also some other problems, e.g. the problem of separating the concession fees from the income tax, the problem of raising the concession fees to 20 per cent of the information price or last but not least the problem of fixing a new proportion of dividing the profits on the 70 : 30 basis. The fight put up by OPEC by exclusively economic means — has no good prospects of success. The best way out of the difficulties seems to be the formation of native capital which would undertake the business of oil extraction and oil distribution. The fight with the world cartel is difficult because of .the political weakness of the oil countries, the anxiety concerning the oil distribution (the world's distribution network is mostly in the hands of the cartel) and the lack of native skilled labour. The attempts to nationalize the oil industry have taken place only in a few countries — they constituted, however, a bold example to the other oil producing countries. Lately the nationalization trend slackened somehow, on the other hand the formation of regional groupings are getting popular. There are at present two such organisations: ARPEL — the Organisation of State Oil Enterprises in Latin American Countries and APO — The Arab Oil Organisation. Of course the mere setting up of new organisations does not yet mean the end of the World Cartel — it does mean, however, that the times where it could control unconditionally the oil resources are definitely over.
The Fight of the Oil Countries against the World Oil Cartel